THE ROLE OF SELF-CONCEPT AND HEALTH LOCUS OF CONTROL ON QUALITY OF LIFE AMONG INDIVIDUALS WITH DIABETES - Octari, Tiara Ersha; Suryadi, Bambang; Sawitri, Dian R. (Jurnal Psikologi, 2020)
Quality of life is an elemental factor for individuals with diabetes to improve health and reduce the risk of complications. Diabetics need to maintain their behavior to control blood sugar. With a locus of control and good self-concept, they will be able to improve their quality of life. The purpose of this study is to examine the role of self-concept and health locus of control on the quality of life among individuals with diabetes. This study used a quantitative approach involving 157 diabetics Jabodetabek. Nonprobability sampling technique, precisely the purposive sampling technique, was used to select the study sample. In collecting the data, three instruments were administered which consisted of a World Health Organization Quality of Life (WHOQOL-BREF) instrument with 26 items (Î± = .92), Revised Generalized Health-Related Self Concept Scale (RGHRSCS) with 25 items (Î± = .76), and Diabetes Locus of Control Scale (DLOCS) with 18 items (mean Î± = .71). The multiple regression analysis applied to answer the research questions. The findings of this study indicate that there was a significant effect of self-concept and locus of health control on the quality of life of people with diabetes. Based on the minor hypothesis test, there were five significant variables, namely disposition of health protector (b=.433, p<.001), motivation to maintain health (b=.176, p=.007), extrinsic motivation avoidance (b=-.141, p=.033), internality (b=.289, p<.001), and other strong externalities (b=.105, p=.017), whereas the other three variables are not significant, specifically vulnerability, health-risky habits, and chance externality.